Updating a Perinatal Risk Scoring System to Predict Infant Mortality - Umer, Amna; Lilly, Christa; Hamilton, Candice; Cottrell, Lesley; Lefeber, Timothy; Hulsey, Thomas; John, Collin (American Journal of Perinatology, 2019)
Objective The Birth Score Project (Project WATCH) began in the rural state of West Virginia (WV) in the United States in 1984. The project is intended to identify newborns with a greater risk of infant mortality. The primary objective of this study was to update the current Birth Score based on current literature and rigorous statistical methodology.Study Design The study merged data from the Birth Score, Birth Certificate (birth years 2008–2013), and Infant Mortality Data (N = 121,640). The merged data were randomly divided into developmental (N = 85,148) and validation (N = 36,492) datasets. Risk scoring system was developed using the weighted multivariate risk score functions and consisted of infant and maternal factors.Results The updated score ranged from 0 to 86. Infants with a score of ≥17 were categorized into the high score group (n = 15,387; 18.1%). The odds of infant mortality were 5.6 times higher (95% confidence interval: 4.4, 7.1) among those who had a high score versus low score.Conclusion The updated score is a better predictor of infant mortality than the current Birth Score. This score has practical relevance for physicians in WV to identify newborns at the greatest risk of infant mortality and refer the infants to primary pediatric services and case management for close follow-up.
Keywords: infants; infant mortality; birth score; West Virginia